2013
DOI: 10.1073/pnas.1222821110
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic recognition and spatial responses by rice roots

Abstract: Root system growth and development is highly plastic and is influenced by the surrounding environment. Roots frequently grow in heterogeneous environments that include interactions from neighboring plants and physical impediments in the rhizosphere. To investigate how planting density and physical objects affect root system growth, we grew rice in a transparent gel system in close proximity with another plant or a physical object. Root systems were imaged and reconstructed in three dimensions. Root-root intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
148
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(152 citation statements)
references
References 41 publications
1
148
1
2
Order By: Relevance
“…One possible explanation arises from reports of chemical signals, such as secondary metabolites or proteins, in root exudates that mediate how a plant root interacts with its soil environment (de Kroon, 2007;Semchenko et al, 2008;Biedrzycki et al, 2010;Badri et al, 2012;Padilla et al, 2013). This agrees with evidence that roots respond to neighboring roots in a genotype-dependent manner, wherein roots of the same genotypes overlapped better, while roots of different genotypes avoided each other potentially via chemical signals (Fang et al, 2013). However, the specific molecular mechanisms involved in these processes and how they influence foliar growth are poorly understood.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…One possible explanation arises from reports of chemical signals, such as secondary metabolites or proteins, in root exudates that mediate how a plant root interacts with its soil environment (de Kroon, 2007;Semchenko et al, 2008;Biedrzycki et al, 2010;Badri et al, 2012;Padilla et al, 2013). This agrees with evidence that roots respond to neighboring roots in a genotype-dependent manner, wherein roots of the same genotypes overlapped better, while roots of different genotypes avoided each other potentially via chemical signals (Fang et al, 2013). However, the specific molecular mechanisms involved in these processes and how they influence foliar growth are poorly understood.…”
Section: Introductionsupporting
confidence: 72%
“…Recent studies using rhizotron imaging, in which special pots are used to allow direct visualization of the roots, of roots grown in soil or artificial media showed that roots perceive the proximity to neighbors and alter their foraging behavior and architecture (Hodge, 2004;Cahill et al, 2010;Nord et al, 2011;Fang et al, 2013). While nutrient depletion is thought to be a key signal for altered root foraging in competitive environments, recent studies have shown that neighboring roots can also trigger changes in root architecture independently of nutrient competition (Padilla et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Root self-discrimination and its consequences for underground competition have been reported [7,9,10,34]. However, the role of self-discrimination in above-ground interactions has largely been ignored (but see [35] for the effect of kin discrimination on above-ground traits).…”
Section: Discussionmentioning
confidence: 99%
“…Root discrimination allows plants to change their root allocation and morphology in response to either self or non-self neighbours [6][7][8][9][10][11][12]. Root discrimination is thought to be mediated by environmentally based physiological coordination rather than by genotype-specific differences as in self-incompatibility and immune systems [7][8][9] (however, see [10]). For example, Gruntman & Novoplansky [9] have demonstrated that clones derived from the same plant become related to each other as genetic aliens after temporal separation.…”
Section: Introductionmentioning
confidence: 99%
“…, 适合度增加 (Tonsor, 1989)。植物的这种行为可以用亲缘选择理 论来解释, 基因上相似度高的个体间可以通过相互 合作减少用于竞争的资源消耗, 从而将更多的资源 投资于繁殖并增加适合度 (Hamilton, 1964a(Hamilton, , 1964bAxelrod & Hamilton, 1981)。当植物的邻居为亲缘株 时, 亲缘选择和生态位分化可能同时起作用, 且两 者作用于同一个过程 (File et al, 2012; Chen et al, 2012;File et al, 2012;Dudley et al, 2013;李洁等, 2014)。目前, 有关植物 亲缘识别的一些研究关注邻株身份如何影响基于植 物繁殖表现的适合度 (Mohana et al, 2001;Milla et al, 2009Milla et al, , 2012Bhatt et al, 2011;Biernaskie, 2011), 另一些关注不同邻株身份对竞争性状及其生物量分 配的影响 (Dudley & File, 2007;Murphy & Dudley, 2009;Bhatt et al, 2011;Lepik et al, 2012;Dudley et al, 2013;Fang et al, 2013;Mercer & Eppley, 2014;Semchenko et al, 2014)。另 外, 地下部分竞争信号在植物身份识别过程中所扮 演的角色得到较多的关注 (Dudley & File, 2007;Murphy & Dudley, 2009;Bhatt et al, 2011;Lepik et al, 2012;Dudley et al, 2013;Fang et al, 2013;Mercer & Eppley, 2014;Semchenko et al, 2014), 少量的研究表明地上部分 竞争信号在植物身份识别过程中也扮演着一定的角 色 (Crepy & Casal, 2015) Chen et al, 2012;Bais, 2015;Crepy & Casal, 2015) ind.·m -2 , 即每小区25株, 植株间距10 cm; 低密度 为36 ind.·m -2 , 即每小区9株, 植株间距16.7 cm。 Fig. 2 Effects of neighbor identity on the morphology and biomass allocation of Setaria italica (mean ± SE).…”
Section: 植物间的正相互作用(互助)和负相互作用(竞 争)是影响群落结构、 多样性和动态的一个重要过程unclassified